2020
DOI: 10.1002/ijc.33447
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic, genomic and protein expression characterization of 356ROS1fusion driven solid tumors cases

Abstract: Based on the approvals of crizotinib and entrectinib by the Food and Drug Administration for the treatment of ROS1 positive nonsmall cell lung cancer (NSCLC), we sought to examine the mutational profile of a variety of solid tumors (excluding sarcomas) with ROS1 fusions that underwent comprehensive genomic profiling. A review of our database was performed to extract all nonsarcoma patients with ROS1 fusions that were discovered by the hybrid capture‐based DNA only sequencing assays. We examined the coalteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…It contained the FERM domain of the EZR protein joined to the transmembrane and kinase domains of ROS1 (178). Additional studies confirmed the recurrence of EZR-ROS1 in lung cancer and also that the finding was clinically important: the chimeric protein could be the target of kinase inhibitors with very good results (160,161,167,169,(179)(180)(181)(182)(183)(184).…”
Section: Chromosomementioning
confidence: 89%
See 4 more Smart Citations
“…It contained the FERM domain of the EZR protein joined to the transmembrane and kinase domains of ROS1 (178). Additional studies confirmed the recurrence of EZR-ROS1 in lung cancer and also that the finding was clinically important: the chimeric protein could be the target of kinase inhibitors with very good results (160,161,167,169,(179)(180)(181)(182)(183)(184).…”
Section: Chromosomementioning
confidence: 89%
“…In 2016, a review of ROS1 fusions in cancer reported 26 genes as having been found to fuse with ROS1 (159) whereas a similar recent review reported the number of ROS1 fusion partners to be 54 (160). In 2020, the year before the review by Drilon et al (160) was published, another 14 novel ROS1 fusion partner genes were added to the list (161)(162)(163)(164)(165), raising the total currently known number of ROS1 chimeras to 68. Regardless of their large number and variability, ROS1 chimeras encode chimeric ROS1 proteins which are constitutively active kinases and which, consequently, may be targets for treatment with kinase inhibitors (13, 160,[166][167][168][169][170][171].…”
Section: Chromosomementioning
confidence: 99%
See 3 more Smart Citations